SERIES OF ONLINE MATHEMATICAL EVENINGS «JOURNEY TO THE STARS: WHY DO MATHEMATICS IN SPACE?» - I.K KONDAUROVA; N.S CHEGODANOVA (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
The 60th anniversary of the human spaceflight is actualized the need to develop a series of online evenings for schoolchildren «Journey to the Stars: Why mathematics in space?». The definition of the concept «intersubject (mathematics + astronomy) mathematical online evening», which we have defined as a remote form of extracurricular work with schoolchildren, which is an artistic, entertaining, cognitive event aimed at expanding mathematical knowledge, developing cognitive interest in mathematics with the help of the leading subject (integrator) of mathematics and an auxiliary subject (astronomy), is clarified in the article . The purpose of the «astromathematics» online evenings is to expand and deepen mathematical knowledge, skills and the formation of elementary astronomical concepts and concepts on their basis. Age of participants of online math evenings: students of grades 1 - 9. Three events: «Conversations about the Universe» (grades 1-4); «Space Travel» (grades 5-6); «Space Quiz» (grades 7-9) is planned to be held for them . One of the events, the online math evening «Space Travel» for grades 5-6 is given in the article. Its purpose is to show how mathematical knowledge is used in astronomy, to form students ' ideas about the development of Russian cosmonautics, to develop a cognitive interest in mathematics and astronomy.